2021
DOI: 10.3390/microorganisms9081608
|View full text |Cite
|
Sign up to set email alerts
|

Family SES Is Associated with the Gut Microbiome in Infants and Children

Abstract: Background: While early life exposures such as mode of birth, breastfeeding, and antibiotic use are established regulators of microbiome composition in early childhood, recent research suggests that the social environment may also exert influence. Two recent studies in adults demonstrated associations between socioeconomic factors and microbiome composition. This study expands on this prior work by examining the association between family socioeconomic status (SES) and host genetics with microbiome composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 85 publications
1
21
0
Order By: Relevance
“…Low SES is associated with illness and reduced life expectancy ( 1 3 ) and also with abnormal microbiomes ( 6 8 ). This paper summarizes evidence that these two observations are linked and that lifestyle factors that accompany low SES can reduce and distort microbial exposures and cause them to diverge from the exposures with which humans coevolved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low SES is associated with illness and reduced life expectancy ( 1 3 ) and also with abnormal microbiomes ( 6 8 ). This paper summarizes evidence that these two observations are linked and that lifestyle factors that accompany low SES can reduce and distort microbial exposures and cause them to diverge from the exposures with which humans coevolved.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have concentrated on children. A study of the gut microbiomes of children with a mean age of 4.5 years found that the bacterial composition was significantly influenced by the SES of parents as determined by educational level ( 6 ). Similarly, a study of fecal samples from a subset ( n = 1,672) of a large cohort of British twins for whom SES data were available ( 7 ), and another study of 139 Arab children of various SESs in Israel ( 8 ), found significant relationships between SES and fecal 16S rRNA microbiome composition.…”
Section: Perspectivementioning
confidence: 99%
“…Participants with lower SES reportedly had lower alpha diversity in gut microbiota, which can influence health factors such as metabolism, gene regulation, and host immune responses ( 128 130 ). In other studies, lower neighborhood SES has been associated with reduced diversity of colonic ( 131 ) and salivary microbiota ( 132 ), and family SES is associated with the gut microbiome in infants and children ( 133 , 134 ).…”
Section: The Microbiome and Infectious Diseasesmentioning
confidence: 89%
“…Much like the observation that NCDs are often linked to socioeconomic position—such that NCDs are disproportionally shouldered by the disadvantaged—research has shown that the composition and diversity of gut (and oral) microbes are similarly associated with socioeconomic position in various populations [ 75 , 76 , 77 , 78 , 79 ]. It is also known that functional changes to the microbiome are mediated by many “lifestyle” factors, including stress [ 80 , 81 , 82 ], sleep [ 83 ], exercise [ 84 ], tobacco use [ 85 ], and, of course, short and long-term dietary choices [ 86 , 87 , 88 ].…”
Section: New Perspectives On the Ecology Of Social Disadvantagementioning
confidence: 99%